A Sociological Approach to Official and Non-Official Audiovisual Translators' Practice in Iran: The Case of Movie Title Translation. Issue 4 (4th July 2022) - Fakharzadeh, Mehrnoosh
ABSTRACT: The present study is an initial attempt at examining the translation strategies employed by two groups of audiovisual translators in rendering movie titles from English to Persian. Adopting Bourdieu's field theory, 206 English movie titles were compared with two Persian titles, one produced by official and the other by non-official translators. The results revealed the dominant strategies used by official and non-official audiovisual translators were significantly different. The results obtained from Chi-square, Cramer's v, and Bonferroni correction tests showed significant differences concerning six translation strategies. The reason may lie in the translators' habitus formed in two subfields of audiovisual translation, namely offline and online subfields.